The change of transformation temperature on NiTi shape memory alloy by pressure and thermal ageing - Kok, M.; Dagdelen, F.; Aydogdu, A.; Aydogdu, Y. (Iop Publishing Ltd, 2016)
We have investigated the effect of pressure and thermal ageing on transformation behavior of Ni-% 45.16Ti shape memory alloy. 70-320 MPa pressure was applied and annealed at 500 degrees C for 2 hour to see the effect of applied pressure on transformation temperature. It was observed that the starting and final temperature of austenit increased, the martensite start temperature almost remain constant and final temperature decreased with the increase of pressure. The interval stress value of NiTi alloy was determined as 13.77 MPa/degrees C during austenite transformation. The transformation temperature of Ni-%45.16Ti alloys after thermal ageing was also investigated. No significant variation in these parameters was obtained. According to XRD measurements, there are two phases namely R (rhombohedral) and B19 (monoclinic) martensite were obtained. We did not see any change on the peaks after ageing.
9th International Conference on Magnetic and Superconducting Materials (MSM) -- APR 30-MAY 03, 2015 -- Antalya, TURKEY